2004
DOI: 10.1081/erc-200036185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyroid Function on LDL Oxidation in Hypothyroidism and Hyperthyroidism

Abstract: Oxidized low-density lipoproteins (LDL) are highly suspected of initiating the atherosclerosis process. Hypothyroidism is frequently associated with hypercholesterolemia and carries increased risk for atherosclerosis. In contrast to hypothyroidism, hyperthyroidism is not associated with increased LDL cholesterol, but is associated with increased oxidized LDL. This study was designed to evaluate the changes in LDL oxidation in subjects with hypothyroidism or hyperthyroidism, and to reveal the effects of treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…While L-T4 treatment can improve dyslipidemia, the long-term effect of the L-T4 load on cardiovascular risk is unknown [ 33 , 34 ]. Overt hyperthyroidism is associated with reduced total- and HDL-cholesterol concentrations [ 35 , 36 ], which normalize after remission of hyperthyroidism [ 37 ]. Several studies have found no difference in lipid profiles in sub-clinical hyperthyroidism [ 38 , 39 ], though reduced cholesterol levels have sometimes been reported in subjects older than 55 years [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…While L-T4 treatment can improve dyslipidemia, the long-term effect of the L-T4 load on cardiovascular risk is unknown [ 33 , 34 ]. Overt hyperthyroidism is associated with reduced total- and HDL-cholesterol concentrations [ 35 , 36 ], which normalize after remission of hyperthyroidism [ 37 ]. Several studies have found no difference in lipid profiles in sub-clinical hyperthyroidism [ 38 , 39 ], though reduced cholesterol levels have sometimes been reported in subjects older than 55 years [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding lipid metabolism, overt hyperthyroidism is associated with decreased plasma concentrations of total and/or LDL cholesterol, 3,[12][13][14][15][16] that normalize after correction of hyperthyroidism ( Table 2). [17][18][19] Subclinical hyperthyroidism is a state, in which the patient has a suppressed thyrotrophin (TSH) level (below 0·4 mU/l), although the free T4 level is within the normal range. This condition affects several organ systems, including bone [20][21][22][23] and the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding lipid metabolism, overt hyperthyroidism is associated with decreased plasma concentrations of total and/or LDL cholesterol, 3,12–16 that normalize after correction of hyperthyroidism (Table 2). 17–19 …”
Section: Introductionmentioning
confidence: 99%
“…On the other side, the oxidation of the LDL-receptor increases, favoring inflammation and oxidative stress as described above [ 80 ]. The lipoprotein lipase activity is also impaired in hypothyroidism with a reduction in the TG clearance and an increase in the circulating VLDL particles [ 87 ]. The synthesis of endogenous cholesterol is not increased but the amount of available cholesterol in the liver is maintained or is even higher because the cholesterol absorption is increased and beta-oxidation in hepatocytes is decreased; the overall effect is a higher VLDL output from the liver [ 88 ].…”
Section: Insulin Resistance Dyslipidemia Inflammatory and Oxidative M...mentioning
confidence: 99%